The Concept of Smart and NZEB Buildings and the Integrated Design Approach. (2017) - Karlessi, Theoni; Kampelis, Nikos; Kolokotsa, Denia; Santamouris, Mat; Standardi, Laura; Isidori, D.; Cristalli, C.
Abstract: As we are nowadays experiencing a transition period for the energy demand, there is a clear movement of the European energy market towards a new field of efficiency including reliable and smart systems that will upgrade the improvement of Europe's economic and environmental health. To this end smart systems introduce innovative applications with multiple and interdisciplinary characteristics: safe integration of additional renewables, distribution to the network, efficient delivery systems and monitoring control through demand response in order to achieve zero energy targets. The integration of smart technologies requires a holistic approach that takes into account all aspects of sustainability. The implementation of highly efficient smart buildings is feasible through the integration of smart metering, renewable systems acting as generators/storage and energy management. The holistic system supports and fulfils demand load management and distribution network of future grids.. Moreover, the benefits of effective thermal and electrical storage are underlined as a crucial factor of smart systems and smart buildings. This paper highlights the principles of integrated design procedure and links the process with smart building technologies. Energy efficiency methodologies and innovative techniques applied at building level are presented. To this context current EU policy framework, trends and perspectives concerning integrated design as a supportive tool for zero energy concept are also provided.